Effect of modified surface and architectonics of porous-permeable TiNi-based alloy scaffold on cellular biocompatibility - O. V. Kokorev (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
Cellular scaffolds based on porous biomaterials play an important role in the engineering of various tissues. Our porous-permeable cellular TiNi-based alloy scaffolds combine the advantages of metal structures, hardness, wear resistance and elasticity similar to that of human tissues. The aim of the research was the study on the change in the surface layer of samples from TiNi-based alloy and on the biotesting of modified samples with the 3H3 fibroblast line. Materials and methods: The biocompatibility of several samples of TiNi-based alloy scaffolds with an average pore size of 83,150,365 μm with modified (acid treatment) surface with 3H3 fibroblast line. Results. The porous-permeable cellular TiNi-based alloy scaffolds (average pore size = 150 μm) modified by treatment with solution of concentrated acids exhibited the highest biocompatibility with a fibroblast culture. It was shown that hemolysis of TiNi-based alloy samples, which are intact and treated with solution of concentrated acids, does not exceed 2 %. Direct cultivation of modified samples with fibroblast line in the cytotoxic test showed low cytotoxicity of the tested cells. The studies carried out using a scanning microscope showed that mesenchymal cells of bone marrow are attached in sufficient quantities to the microporous surface of the modified samples, which allows them to grow and proliferate in the pore space of TiNi-based alloy scaffolds and to cultivate tissue in vitro. Conclusion. Samples of scaffolds manufactured by the SHS-method and modified by treatment with concentrated solution of acids are technological and perspective biomaterial for their use as implantable clinically useful scaffolds.